Dynamic Capabilities in Healthcare: The Crucial Role of Adaptability in Enterprise Risk Management for Indonesian Hospitals - Yaya, Rizal; Saud, Ilham Maulana; Murtin, Alek; Putra, Adli Zuliansyah; Suryanto, Rudy; Sofyani, Hafiez (YCAB Publisher, 2025)
Background: The healthcare sector, particularly hospitals, encounters significant challenges that necessitate the implementation of robust risk management strategies. Maintaining the sustainability and performance of private hospitals is especially critical, given their pivotal role in delivering healthcare services. Objective: The purpose of this study is to investigate whether adaptability is a variable that can improve ERM and to determine the extent and relationship between ERM and performance and sustainability of private hospitals in Indonesia. Methods: A self-administered questionnaire which was sent to 58 hospitals online and filled in by the board members of the respective hospitals including the directors or upper and middle management. The analysis of the gathered data was conducted through Structural Equation Modeling-Partial Least Squares analysis. Result: The efficiency of ERM has been evidenced whereby it has a direct impact on hospital’s performance and sustainability. In addition, it can be observed that the study findings confirm that adaptability is a predictor variable of ERM, where adaptability is a prerequisite to enable ERM to have a positive influence on the performance and sustainability of Indonesian private hospitals. Conclusion: This study provides evidence of the importance of the dynamic capabilities theory as a framework to assess the significance of adaptability to the implementation of ERM in Indonesian hospitals. Keywords: adaptability; enterprise risk management; hospital; performance; sustainability